(untitled) (Journal of Fiber Bioengineering and Informatics, 2008)
The extracted components of Chinese medicine were prepared by following different methods and were used to make microcapsules of the medicine. The two agent samples of the nano- Chinese medicine microcapsule agent and the Chinese medicine Microcapsule agent and two treated fabrics, was used to determine the anti-virus properties of influenza virus and Herpes simplex virus by fluorescent quantification polymerase chain reaction (FQ-PCR). The testing conditions included the agent concentrations of original liquid, 1/10, 1/100, 1/1000 and 1/10000, and virus contents of 5.00 &#215 107, 5.00 &#215 105, 5.00 &#215 103, 5.00 &#215 102copies/ml. The results indicated that all of the two agent samples of the nano-Chinese medicine microcapsule agent, the Chinese medicine microcapsule agent and the treated fabrics have good anti-virus characteristics. The nano-Chinese medicine microcapsule agent was more effective than the Chinese medicine microcapsule agent. The original style and good properties of the woollen fabrics were basically kept.